PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode Tahun 2012-2014) - Fanny Anggraeny, 12.05.52.0011; Aini, Nur (Students' Journal of Accounting and Banking, 2016)
This study aimed to axamine the impact of the characteristics of good corporate governance as institutional ownership, managerial ownership, the proportion of independent commissioners, the number of boards of directors, the size of audit committee, the number of audit committee meetings, and a number of financial experts on audit committee the possibility of financial distress on companies listed in Indonesia Stock Exchange period 2012-2014. The sampling method used purposive sampling with the obsevation period from 2012 to 2014. Criteria for financial distress company is a company with negative earnings per share in the reporting period. Relationship and (or) influence between variable is described by using logistic regression analysis. The results of anlysis showed that the variables of number of board of directors in a significant negative effect on the possibility of financial distress, while variable institutional ownership, managerial ownership, the proportion of independent commissioners, the size of the audit committee, the number of audit committee meetings, and the number of audit committee financial expert did not significantly affect the financial distress.Keywords: Financial Distress, Corporate Governance, Earnings Per Share